Rancang bangun sistem fids-pas terintegrasi berbasis esp32 di bandara kuala pembuang - Richardo Pratmana Maha; Muh. Wildan; Toni (Jurnal Pengetahuan dan Pendidikan, 2026)
This research focuses on the design and implementation of an integrated Flight Information Display System (FIDS) and Public Address System (PAS) based on the Internet of Things (IoT). The main problem addressed is the separation between visual and audio flight information delivery in some airports, which can lead to information inconsistency for passengers.The research method used is Research and Development (R&D), which includes system design, expert design validation, system implementation, and functional testing. The system is developed using a web-based backend with a MySQL database running in a Docker container environment. Data communication between the backend system and the PAS device is carried out using the MQTT protocol. The PAS system is implemented using an ESP32 microcontroller connected to a DFPlayer Mini audio module.The testing results indicate that the integrated FIDS–PAS system is able to deliver synchronized visual and audio flight information according to changes in flight status. The system is also capable of performing automatic announcements without manual operator intervention. Therefore, the developed system can be used as a prototype of an IoT-based integrated flight information system.